Equality in higher education partnerships: defining the concept in divergent contexts - Hagenmeier, Conrad Cornelius Andreas (Department of Commercial Law, 2022)
This thesis investigates how an appropriate theoretical framework for equal partnerships between universities in divergent contexts could be formulated, based on the principle of substantive equality. Literature has to date not addressed whether equality should be a principle underlying higher education partnerships, and the concept of equality in higher education partnerships has not yet been defined. This thesis explores present practices and conceptualisations of equality, specifically in partnerships between higher education institutions of divergent strengths, through a literature study, a survey of university stakeholders responsible for the management of bilateral international university partnerships, four minicase studies and a doctrinal review of the South African Constitutional Court's equality jurisprudence. An interpretivist paradigm is applied; Fredman's four-dimensional understanding of substantive equality serves as its theoretical framework. The internet-based survey tool ‘SurveyMonkey' was used to collect data for the survey. Data evaluation was undertaken using the analytical tools embedded in SurveyMonkey, the Statistical Programme for the Social Sciences (SPSS), and qualitative data was thematically analysed. The mini-case studies applied present practices and conceptualisations of equality in higher education partnerships, specifically in those between higher education institutions of divergent strengths, as the primary unit of reference. The substantive equality jurisprudence of the South African Constitutional Court was evaluated using Fredman's four-dimensional model of substantive equality. The most notable insight from the empirical research is that there is no uniform understanding of equality in higher education partnerships. Based on the empirical and doctrinal research, a theoretical framework was formulated. For partnerships to be considered equal, certain criteria from an open-ended list should be met, which include a value-foundation in mutuality, transparency and accountability, trust, equity and fairness, academic freedom, promotion of education, research and development, and ubuntu. Partners should make contributions that are equally meaningful, considering their context. They should be able to achieve their priorities to an equal extent through the partnership. The partners should recognise and affirm their equal worth, as well as the equal worth of all those who participate in partnership activities in all spheres of the collaboration. Open and transparent communication should be practised, and partnership decision-making processes should equally weigh all partners' voices and ensure that minority views are considered. The partnership as a whole should affirm the diversity of partner universities.